Predation with the tongue through viscous adhesion, a scaling approach. Issue 10 (23rd February 2017) - Houze, Maurine; Damman, Pascal
Abstract : Combining experimental and theoretical approaches, we develop a new framework to study adhesion in biological systems. A theoretical model was obtained from a detailed analysis of viscous adhesion in a probe-tack geometry. A comparison of the obtained scaling model with in vivo measurements was done to confirm the validity of the predation mechanisms based on viscous adhesion. Abstract : Some predators, mainly lizards and amphibians, capture their prey with their tongue. The process of capture involves strong adhesion mechanisms to overcome inertial forces that should be related to a viscous mucus produced at the tongue tip. A scaling model of prey capture independent of the anatomic details of the animals is developed from a study of viscous adhesion with a probe-tack geometry. This model is then successfully applied to describe the nonlinear evolution of the maximum prey size with the predator length for chameleons. This approach of prey capture defines a new framework that should help biophysicists and biologists to study more quantitatively the adhesion mechanisms for various animals and biological processes.